School amalgamation and wellbeing for LGBTQ+ students: A scoping review protocol - Luke Slattery; Daragh Bradshaw; Sarah Jay; Aisling T. O’Donnell; Lynn Fenton (PLoS ONE, 2025)
Introduction School amalgamations, or the merging of two or more pre-existing schools, are typically conducted in response to resource constraints. While merging existing schools can be financially beneficial, the wellbeing of marginalised students, such as those who identify as LGBTQ+ , may be at risk. Evidence on the impact that school amalgamation may have for LGBTQ+ students’ wellbeing has not been consolidated in a review. The proposed scoping review aims to identify empirical studies which measure the impact of school amalgamation on the wellbeing of LGBTQ+ students, to document the methodologies they use, and to identify challenges faced by LGBTQ+ students in amalgamated schools. Methods This review will be conducted in line with the JBI Manual for Evidence Synthesis and PCC framework. Searches will be conducted in multidisciplinary databases and relevant citations exported to Covidence. Articles will be screened against inclusion and exclusion criteria by two independent reviewers. Results Relevant studies will be charted and synthesised for inclusion in the final scoping review. Particular attention will be given to the scope of existing literature relating to the review question, methodological trends, and areas for further study.